Designand Development of Thermally Enhanced Textile Nanocomposites Incorporated with Phase Change Material Nanowe - Karaoğlu, Emel Önder; SARIER, NİHAL (My University, 2019)
Solid-liquid organic phase change materials (PCMs) have the ability to absorb and release large amounts of latent heat during melting and solidification processes, thereby creating a buffer effect against temperature changes. When a textile product is incorporated with PCMs, it can provide an enhanced thermal capacity in addition to the existing passive insulation characteristic of the structure. A variety of encapsulating processes have been applied to PCMs before integrating them into different composites to prevent their interaction with the surrounding medium, to increase their mechanical and thermal stabilities and to enhance their ease of handling. In recent times, the coaxial electrospinning technique has been employed as a simple technique for generating form-stable PCMs. These nanowebs possess remarkable advantages such as preventing PCM’s dispersion in the structure, formation of large surface area by the numerous nanofibers, light weight, and direct use in various composites. The aim of this study is to produce shape stabilized PCM nanowebs by coaxial electrospinning as thermal energy storage materials and to seek their potential use in textile based composites. Poly (acrylo nitrile) (PAN) was chosen as the shell material, considering its non-reactivity with the core material as well as its suitability for the manufacture of ultra-fine fibres in textile engineering applications. Poly(ethylene glycols) (PEGs), namely PEG 1000 and PEG 1500 were used as core materials, owing to their capability for repeatable solid-liquid phase changes at low and moderate temperature intervals, high heat of fusion (AHfus), non-volatility, chemical and thermal stability, solubility both in water and organic solvents, biocompatibility, non-toxicity and low price. The phase change enthalpies of PAN-PEG1000 and PAN-PEG1500 nanowebs, all electrospun using 40 w% core and 6 w% shell solutions in dimethyl acetamide, were found as 91 Jg’1 between 28-41 °C, 105 Jg’1 between 44-53 °C a during heating for 10 cycles. To seek the potential use of PAN-PEG nanowebs (NW) in textile-based composites, two sandwich-like structures (felt layer: bonding layer: NW: bonding layer: felt layer), DI and D2, were developed and characterized for their thermal properties. The heat capacities of DI and D2 were 81 Jg’1 between 33^-6 °C, 48 Jg’1 between 46-54 °C. The PAN-PEG nanowebs as well as the felt nanocomposites are promising for further manufacturing practices in the area of thermal management across various industries.